Biological effects of metal degradation in hip arthroplasties. (7th February 2018) - Granchi, Donatella; Savarino, Lucia Maria; Ciapetti, Gabriela; Baldini, Nicola
Abstract: Metals and metal alloys are the most used materials in orthopedic implants. The focus is on total hip arthroplasty (THA) that, though well tolerated, may be associated with local and remote adverse effects in the medium-long term. This review aims to summarize data on the biological consequences of the metal implant degradation that have been attributed predominantly to metal-on-metal (MoM) THA. Local responses to metals consist of a broad clinical spectrum ranging from small asymptomatic tissue lesions to severe destruction of bone and soft tissues, which are designated as metallosis, adverse reactions to metal debris (ARMD), aseptic lymphocytic vasculitis associated lesion (ALVAL), and pseudotumors. In addition, the dissemination of metal particles and ions throughout the body has been associated with systemic adverse effects, including organ toxicity, cancerogenesis, teratogenicity, and immunotoxicity. As proved by the multitude of studies in this field, metal degradation may increase safety issues associated with THA, especially with MoM hip systems. Data collection regarding local, systemic and long-term effects plays an essential role to better define any safety risks and to generate scientifically based recommendations.